Effect of rifampicin on the kidney of albino rats - DE Peters; AO Chike (Journal of Applied Sciences and Environmental Management)
The study was designed to investigate the effect of rifampicin on the kidney biomarkers and histopathology of kidney of albino rats. 42 albino rats were used and rifampicin was administered at 1.10mg/120gBW and 0.55mg/120gBW for intervals of 20, 40 and 60days.Animals were sacrificed 24 hours after the last day of administration and blood samples were collected for the estimation of urea and creatinine levels sodium , potassium, chloride and bicarbonate ion concentrations. Result from this study indicates that urea and creatinine levels in a dose and time dependent manner, significantly increased (p<0.05) all through the duration of the study when compared with the control value. Significant decrease (p<0.05) was observed for sodium ion concentration in a dose and time dependent manner also while potassium, chloride and bicarbonate ions were non significantly changed (p>0.05). Histological examination of the kidney revealed an inflammation of the glomeruli for 1.10mg/120gBW treated group in 60days. In conclusion, prolonged treatment of tuberculosis patients with rifampicin could result to nephrotoxicity.